Evaluation of Fertilizer Management Approaches in Maintaining Soil Fertility and Plant Nutrient Content in Coffee-Based Agroforestry Systems - Silvia Febiona; R Muhammad Yusuf Adi Pujo Nugroho; Sri Rahayu Utami; Syahrul Kurniawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Application proper type and dose of fertilizer will maintain soil fertility and help coffee growing better in the agroforestry system. Mis-management in fertilization compromises soil quality, and therefore it is underscoring the imperative to ascertain proper type and dosage of fertilizer for maintaining soil properties and nutrient storage. The study aims to assess and evaluate the role of fertilizer management in influencing soil properties, nutrient stocks, and leaf nutrient content. The field experiment was conducted in smallholder coffee agroforestry systems East Java – Indonesia. A randomized block design including a control plot in the protected area and nine combinations of fertilizer types (i.e., organic, inorganic, and mixed) and doses (i.e., low, medium, and high), with three replications, was applied to coffee trees in an agroforestry system. This study proves that differences in fertilizer management did not significantly changes soil physical properties (i.e., soil bulk density and total porosity), indicated that changing in soil physical properties occurred in the long time. In addition, the reduced fertilizer dose (the low dose fertilizer application) had comparable soil available P, and higher soil exchangeable K and soil P stock as compared to those in the protected areas. The study revealed that applying low-dose mixed fertilizer management effectively improved soil fertility.